ANALYSIS OF LONG-TERM VARIATIONS IN THE GEOMAGNETIC POLOIDAL FIELD INTENSITY AND EVALUATION OF THEIR RELATIONSHIP WITH GLOBAL GEODYNAMICS - Biggin A.J.; Thomas D.N. (My University, 2003)
The 1167 published cooling unit (CU) palaeointensity estimates contained in the 400–10 Ma portion of the PINT global database were rigorously filtered according to accurate age determinations, palaeodirectional reliability, recognition of polarity and the method of palaeointensity acquisition. The remaining 865 estimates (group 1) were further filtered to ensure self-consistency, reducing the data set to 425 estimates (group 2). Group 1 and 2 data were clustered into temporally and/or spatially distinct rock suites (RS) enabling each part of the record to be assessed for potential biasing by overrepresentation of palaeosecular variation (PSV). The record was segmented according to the distribution of the data, rather than using arbitrary time windows, to ensure quasi-consistent behaviour within each segment. Differences between these segments clearly indicate that a significant long-timescale (10⁷ and 10⁸ yr) variation of the mean geomagnetic poloidal field intensity (GPFI) occurred during the 400–10 Ma period and hence that changing lowermost mantle conditions affect the capacity of the geodynamo to generate a poloidal field. Both the mean dipole moment and its standard deviation appear to be a function of the range of values each CU may adopt at one particular time. This range is itself controlled by the variation of the maximum limit of dipole moment, while the value of the minimum limit remains relatively constant. Tentative support is provided for the recent suggestion that PSV may have been reduced during the Cretaceous normal superchron (CNS), though more data are needed in the range 120–60 Ma to confirm this. No conclusive evidence was found to support the suggestion that the GPFI record may be biased towards low or high values by palaeointensity determinations obtained using methods that do not adopt pTRM checks. Indeed, offsets caused by unreliable data in well-represented parts of the record are likely to be random and cancel one another out.
Keywords: global geodynamics; palaeointensity variations; Pangaea evolution; reversal frequency